2018
DOI: 10.1088/1748-9326/aaa9c6
|View full text |Cite
|
Sign up to set email alerts
|

The Water-Energy-Food Nexus: A systematic review of methods for nexus assessment

Abstract: The water-energy-food (WEF) nexus is rapidly expanding in scholarly literature and policy settings as a novel way to address complex resource and development challenges. The nexus approach aims to identify tradeoffs and synergies of water, energy, and food systems, internalize social and environmental impacts, and guide development of cross-sectoral policies. However, while the WEF nexus offers a promising conceptual approach, the use of WEF nexus methods to systematically evaluate water, energy, and food inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
477
2
14

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 606 publications
(495 citation statements)
references
References 105 publications
2
477
2
14
Order By: Relevance
“…In practice, social science was under-represented and there was a preference for quantitative (rather than qualitative) methods. This mirrors the findings of the FEW review by Albrecht et al (2018) which found that nearly three-quarters of the studies relied on quantitative approaches.…”
Section: Few Conceptual Paperssupporting
confidence: 79%
See 2 more Smart Citations
“…In practice, social science was under-represented and there was a preference for quantitative (rather than qualitative) methods. This mirrors the findings of the FEW review by Albrecht et al (2018) which found that nearly three-quarters of the studies relied on quantitative approaches.…”
Section: Few Conceptual Paperssupporting
confidence: 79%
“…Open and participatory model development builds familiarity, confidence and acceptance in the models and enables a more diverse group of participants to engage (van den Belt 2004). Albrecht et al (2018) highlighted these 'digital sharing platforms' (e.g. Wolfe et al 2016) as promising means of communicating nexus complexity to diverse stakeholders.…”
Section: Governance and Policymentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is a consensus on the need for managing FEW resources as a FEW nexus, methods for doing so are relatively underdeveloped (Biggs et al, 2015;Mcgrane et al, 2018;Perrone & Hornberger, 2014). Statistical and data analysis techniques used to quantify some interrelationships of the FEW nexus have generally applied "black box" approaches (Ozturk, 2017;Zaman et al, 2017) and often did not include critical components such as social-economic factors leading to incomplete evaluation of nexus interactions (Albrecht et al, 2018). For example, Sušnik, (2015Sušnik, ( , 2018 used global data to regress the countries' gross domestic product (GDP) against total/sectoral water withdrawals, total/specific crop production, and electricity consumption/generation, finding strong correlations between GDP per capita and all three resources metrics.…”
Section: Introductionmentioning
confidence: 99%
“…Fundamental elements of integrated FEWS include uncertainty, the interdependence between sectors, risk and impact of climate change, and a generalized framework that enables scalability to a multitude of applications (Howarth andMonasterolo 2016, Cai et al 2018). A recent review paper by Albercht, Crootof, and Scott (2018) identifies two fundamental gaps in FEWS analysis: (1) the methods are generally not reproducible and are problem-specific; (2) they usually fall short of incorporating the interdependence across sectors as well as resource interdependence. More specifically, recent literature in FEWS management either focus on optimizing the food process and identifying optimal strategies for such management, or focus on the flow of information and resources among the different sectors involved in the operations, ignoring the optimization of the process due to computational complexity.…”
Section: Introductionmentioning
confidence: 99%